The carbon fraction in biomass and organic matter in boreal open woodlands of Eastern Canada. Issue 4 (2nd October 2019) - Boucher, Jean-François; Tremblay, Pascal; Lefebvre, Alexandre; Fradette, Olivier; Bouchard, Sylvie; Lord, Daniel
ABSTRACT: In Canada, boreal open woodlands (OWs) show interesting afforestation potential, but no detailed study is available regarding the carbon fraction (CF) of dry matter in biomass and litter reservoirs (tonne C/tonne dry mass). This study aimed at providing the very first specific CF values of C reservoirs and compartments in OWs, with the main hypothesis that given the particular stand characteristics of OWs, more precise CF values than IPCC's default values would significantly change the calculation of C stocks in OWs. Results indicate that even though the CF values measured in this study were significantly different among the different C reservoirs and compartments in OWs, they matched the IPCC default CF values for the biomass (0.50) and humus (0.37) reservoirs. Therefore, the main hypothesis of this study – that more precise CF values than IPCC's default values would significantly change the calculation of C stocks in OWs – was not supported by the results. Consequently, the IPCC default values of the CF in the biomass and litter (humus) reservoirs can be used to estimate C stocks in boreal OWs, for example when using OWs as the baseline scenario in afforestation projects.